Mass transfer kinetics and mechanisms of phosphate adsorbed on waste mussel shell - Abdul Salim, Nur Atikah; Fulazzaky, Mohamad Ali; Puteh, Mohd Hafz; Khamidun, Mohd Hairul; Mohd Yusof ·, Abdull Rahim; Abdullah, Noorul Hudai; Fulazzaky, Mohammad; Zaini, Muhammad Abbas Ahmad (Springer, 2022)
An excessive amount of phosphate (PO4 3−) released from domestic wastewater treatment plant efuent (DWTPE) may trigger eutrophication of water causing a degradation of healthy aquatic ecosystem. Even though the PO4 3− ions can be removed from aqueous solution with an adsorption technique using the low-cost adsorbent, the adsorption kinetics of PO4 3− removal must be understood. The bed depth service time (BDST), Thomas and modifed mass transfer factor (MMTF) models were used to investigate the adsorption kinetics of PO4 3− removed from DWTPE onto the waste mussel shell (WMS) applied to hybrid plug fow column reactor (HPFCR). Dynamic adsorption capacity of WMS described by the new modifed BDST model is shown to increase with increasing of the plug fow column (PFC) bed. The analysis of mass transfer behavior described using the Thomas model is able to predict the performance of HPFCR at certain depths of the PFC bed. The use of the MMTF models could be useful to describe the real diference between the behaviors of flm mass transfer and porous difusion. The resistance of PO4 3− mass transfer depending on porous difusion has been verifed to provide a contribution in the development of advanced WMS adsorbent for enhancing the HPFCR performance in the future.